Bleaching Earth Recovery from Waste to Purify Cooking Oil by Extraction–Activation Method: - - Caecilia Pujiastuti; Ketut Sumada; Meriana Armidianti; Adinda Rimarsya Bahita Ahmad (2477 - 6165, 2022)
Bleaching Earth is another term used for a type of clay or clay that has a montmorillonite structure. Activation by means of physics, namely heating, can remove dirt and moisture content in the bleaching soil particles. This study aims to reactivate Spent Bleaching Earth (SBE) so that it does not become waste in the surrounding environment. As well as knowing the results of the characteristics of Reactivated Bleaching Earth (RBE) obtained. The reactivation process consists of 2 stages, namely extraction on SBE with n-hexane and activation using a furnace. The method used was maceration extraction with extraction times of 60, 90, 120, 150, 180 and 210 minutes. And the activation temperature is 500, 550, 600, 650, 700 and 750 ˚C. This research gives the result that thermal activation using the furnace can reactivate SBE so that it can match the existing Bleaching Earth characteristics. The best conditions for RBE based on the National Standardization Agency (BSN) in this study were the extraction time of 120 minutes and an activation temperature of 550 oC with a water content value of 0.1625%, real density 2.2970 gr/mL, pH 7.1, and yield. SEM is smoother than others.